2011
DOI: 10.1139/f10-156
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony in marine growth among Atlantic salmon (Salmo salar) populations

Abstract: More synchronous growth was observed between close, than more distantly separated populations of Atlantic salmon (Salmo salar), during both the first and the second year at sea. The marine growth of seven Norwegian populations, located between 608N and 708N, were correlated with sea surface temperatures (SSTs) in the Barents Sea, the Norwegian Sea, and the North Sea, and it was found that growth correlated best with the water temperatures in the area located closest to their home river. Growth was also compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…Factors common to all stocks during the feeding migration include changes in the sea environment, such as the sea surface temperature, conditions in the feeding area, such as the availability of food, and the offshore and coastal fishery. This reasoning has proved correct in several previous studies related to salmon abundance, growth, and migration distance, in which synchronous trends have been related to common environmental factors [6,13,62,63]. The decrease in the proportion of old males has also been observed previous studies , as Järvi [64] reported approximately 11% of the spawners to be 4-6 SW salmon in the 1930s and 1940s, but an analysis sixty years later reported only 0.5-2% of salmon of that age [15].…”
Section: Spawning Age Variation Caused By the Natural Environmentmentioning
confidence: 63%
“…Factors common to all stocks during the feeding migration include changes in the sea environment, such as the sea surface temperature, conditions in the feeding area, such as the availability of food, and the offshore and coastal fishery. This reasoning has proved correct in several previous studies related to salmon abundance, growth, and migration distance, in which synchronous trends have been related to common environmental factors [6,13,62,63]. The decrease in the proportion of old males has also been observed previous studies , as Järvi [64] reported approximately 11% of the spawners to be 4-6 SW salmon in the 1930s and 1940s, but an analysis sixty years later reported only 0.5-2% of salmon of that age [15].…”
Section: Spawning Age Variation Caused By the Natural Environmentmentioning
confidence: 63%
“…Jensen et al (2011) demonstrated that PSG decreases from south to north, whereas daily growth rates are about the same. The main reason for this is that Atlantic salmon smolts migrate to sea earlier in spring in the south than further north and hence experience a longer growth season at sea as postsmolts (Hvidsten et al 1998;Kennedy and Crozier 2010;Jensen et al 2012a).…”
Section: Age and Growthmentioning
confidence: 96%
“…To obtain long time-series with high temporal and spatial resolution of directly measured ocean properties, especially for geographically remote or inaccessible locations, behavioural studies generally have relied on optimal interpolated gridded fields of remotely-sensed satellite data of, for example, SST and sea level anomaly (Bradshaw et al 2004, Todd et al 2008, Jensen et al 2011. One major advantage of these data sources lies in their allowing a synoptic overview of changing features over large areas.…”
Section: Introductionmentioning
confidence: 99%
“…Bradshaw et al 2004, Jensen et al 2011. Recent studies have linked primary production to both seasonal and interannual ocean variability (Gomes et al 2000, Chavez et al 2011, and time-series variation of the reproduction and abundance of high trophic level consumers in response to ocean climate variation (Mills et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation